Differential physiological and production responses of C3 and C4 crops to climate factor interactions - Opoku, Emmanuel; Sahu, Pranav Pankaj; Findurová, Hana; Holub, Petr; Urban, Otmar; Klem, Karel (Frontiers in Plant Science, 2024)
This study examined the effect of the interactions of key factors associated with predicted climate change (increased temperature, and drought) and elevated CO2 concentration on C3 and C4 crop representatives, barley and sorghum. The effect of two levels of atmospheric CO2 concentration (400 and 800 ppm), three levels of temperature regime (21/7, 26/12 and 33/19°C) and two regimes of water availability (simulation of drought by gradual reduction of irrigation and well-watered control) in all combinations was investigated in a pot experiment within growth chambers for barley variety Bojos and sorghum variety Ruby. Due to differences in photosynthetic metabolism in C3 barley and C4 sorghum, leading to different responses to elevated CO2 concentration, we hypothesized mitigation of the negative drought impact in barley under elevated CO2 concentration and, conversely, improved performance of sorghum at high temperatures. The results demonstrate the decoupling of photosynthetic CO2 assimilation and production parameters in sorghum. High temperatures and elevated CO2 concentration resulted in a significant increase in sorghum above- and below-ground biomass under sufficient water availability despite the enhanced sensitivity of photosynthesis to high temperatures. However, the negative effect of drought is amplified by the effect of high temperature, similarly for biomass and photosynthetic rates. Sorghum also showed a mitigating effect of elevated CO2 concentration on the negative drought impact, particularly in reducing the decrease of relative water content in leaves. In barley, no significant factor interactions were observed, indicating the absence of mitigating the negative drought effects by elevated CO2 concentration. These complex interactions imply that, unlike barley, sorghum can be predicted to have a much higher variability in response to climate change. However, under conditions combining elevated CO2 concentration, high temperature, and sufficient water availability, the outperforming of C4 crops can be expected. On the contrary, the C3 crops can be expected to perform even better under drought conditions when accompanied by lower temperatures.